Cognitive load theory - Plass, Jan L. 1968-; Moreno, Roxana; Brünken, Roland 1965- (Cambridge University Press, 2010)
Cognitive load theory (CLT) is one of the most important theories in educational psychology, a highly effective guide for the design of multimedia and other learning materials. This edited volume brings together the most prolific researchers from around the world who study various aspects of cognitive load to discuss its current theoretical as well as practical issues. The book is divided into three parts. The first part describes the theoretical foundations and assumptions of CLT, the second discusses the empirical findings about the application of CLT to the design of learning environments, and the third part concludes the book with discussions and suggestions for new directions for future research. It aims to become the standard handbook in CLT for researchers and graduate students in psychology, education, and educational technology
Keywords: Cognitive learning; Educational psychology; Informationsverarbeitung; Pädagogische Psychologie; Lehr-Lern-Forschung; Kognitive Psychologie; Aufsatzsammlung